Peran Kompetensi Soft Skills Digital Native dalam Meraih Kesuksesan dalam Berkarir di Dunia Kerja - Olivia Shafitri; Novien Rialdy (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The digital era has created a generation of digital natives with superior technology adaptability. However, to achieve success in the world of work, soft skills competencies remain an important factor that supports individual success. This study aims to explore the role of soft skills competencies in digital natives in building a successful career. Using a qualitative approach, data was collected through in-depth interviews with young digital native workers in various industry sectors. The results showed that interpersonal communication skills, teamwork, adaptability, and time management were the main elements that contributed to their success. The findings highlight the importance of synergy between technical and soft skills in facing the complex challenges of the world of work. The implications of this study offer insights for organizations to develop training programs that are holistic and support the development of soft skills as part of a human capital capacity building strategy.